Anti-inflammatory activity of phenolic extracts from different parts of prickly pear on lipopolysaccharide-stimulated N13 microglial cells - Makhlouf Chaalal; Elena Gavilán; Hayette Louaileche; Diego Ruano; Juan Parrado; Angélica Castaño (International Journal of Phytomedicine, 2015)
Phytochemicals with health-promoting activities that are components of human diet, have shown to exert a protective effect on the CNS under pathological conditions. In this sense, prickly pears exhibit analgesic and anti-inflammatory properties with neuroprotective effect. The purpose of this study was to evaluate the potential protective effect of phenolic extracts from different parts of prickly pear on the production of pro-inflammatory mediators by lipopolysaccharide (LPS) -stimulated N13 microglia. Activation of microglia, the hallmark of neuroinflammation, is key to host defence and tissue repair in brain. However, activated microglia secretes cytokines and other factors that are known to contribute to neurodegeneration. To preserve brain integrity, therefore, it is important to keep microglia activation under strict control. The results show that the extracts studied significantly inhibited the release of pro-inflammatory cytokines such as tumor necrosis factor-alpha (TNF-α), interleukin 1-beta (IL-1β), and inducible nitric oxide synthase (iNOS). The present study, however, does not show a clear linear correlation between antioxidant compounds content (total phenolic and flavonoid contents) and anti-inflammatory activity indicates that there must be some additional components within the extracts that play a pivotal role in the anti-inflammatory effect and therefore further characterization is needed. The present study does, however, demonstrate that the phenolic extracts from different parts of prickly pears are potent inhibitors of microglial activation and thus a potential preventive therapeutic agent for neurodegenerative diseases involving neuroinflammation.